Respuesta :

Multiply the entire equation by three to get 4 + r + 5 = 11. 

r = 2. 
Here's to break it down

Simplifying
2(3r + 4) + -3(r + 1) = 11

Reorder the terms:
2(4 + 3r) + -3(r + 1) = 11
(4 * 2 + 3r * 2) + -3(r + 1) = 11
(8 + 6r) + -3(r + 1) = 11

Reorder the terms:
8 + 6r + -3(1 + r) = 11
8 + 6r + (1 * -3 + r * -3) = 11
8 + 6r + (-3 + -3r) = 11

Reorder the terms:
8 + -3 + 6r + -3r = 11

Combine like terms: 8 + -3 = 5
5 + 6r + -3r = 11

Combine like terms: 6r + -3r = 3r
5 + 3r = 11

Solving
5 + 3r = 11

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 3r = 11 + -5

Combine like terms: 5 + -5 = 0
0 + 3r = 11 + -5
3r = 11 + -5

Combine like terms: 11 + -5 = 6
3r = 6

Divide each side by '3'.
r = 2

Simplifying
r = 2
ACCESS MORE